2011
DOI: 10.3917/rne.034.0235
|View full text |Cite
|
Sign up to set email alerts
|

La batterie d'évaluation des connaissances sémantiques du GRECO (BECS-GRECO) : validation et données normatives

Abstract: Distribution électronique Cairn.info pour John Libbey Eurotext. © John Libbey Eurotext. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…A series of individual tests or batteries of tests tapping semantic (i.e., context‐free) memory was used to extensively assess Patient KA's abilities. The BECS‐GRECO battery (Merck et al, ) is a French battery of five tests assessing semantic knowledge about objects, either living entities ( n = 20) or manufactured objects ( n = 20), matched on various dimensions and presented in both verbal (words) and visual (line drawings) modalities. The Mill Hill Vocabulary test (Raven, Court, & Raven, ) is a well‐known graded‐difficulty test requiring participants to select the correct synonym for each of 44 words (only Part B was administered) from a list of six alternatives.…”
Section: Semantic Memory Retrievalmentioning
confidence: 99%
“…A series of individual tests or batteries of tests tapping semantic (i.e., context‐free) memory was used to extensively assess Patient KA's abilities. The BECS‐GRECO battery (Merck et al, ) is a French battery of five tests assessing semantic knowledge about objects, either living entities ( n = 20) or manufactured objects ( n = 20), matched on various dimensions and presented in both verbal (words) and visual (line drawings) modalities. The Mill Hill Vocabulary test (Raven, Court, & Raven, ) is a well‐known graded‐difficulty test requiring participants to select the correct synonym for each of 44 words (only Part B was administered) from a list of six alternatives.…”
Section: Semantic Memory Retrievalmentioning
confidence: 99%
“…They had no cognitive impairment as assessed with the Mini Mental State Examination (Folstein et al 1975) and the Frontal Assessment Battery (Dubois et al 2000). They all underwent a French verbal semantic matching test adapted from the word-written version of the PPT test (Merck et al 2011) and showed no impairment. The experiment was approved by the local ethics committee.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that the items that failed in one task were not systematically the same in the other task. Her performance was also severely deficient in verbal and nonverbal associative knowledge tasks (word/picture from the BECS GRECO, the "Batterie d'évaluation des connaissances sémantiques du groupe de réflexion sur les évaluations cognitives") (Merck et al, 2011), where a target word/picture had to be matched with another one from two. For example, she matched a "turtle" with an "acorn" (and not with the target "salad").…”
Section: Semantic Assessmentmentioning
confidence: 99%
“…The patient had difficulty to discriminate between real and unreal animals, with a clear tendency to consider nonexisting animals as real. As a further assessment of object recognition, we also administered a test of identity matching (BECS-GRECO (Merck et al, 2011)) measuring the ability to classify two visually different forms of an object as the same object, ability known to be vulnerable to semantic impairment (Ikeda, Patterson, Graham, Lambon Ralph, & Hodges, 2006). In this task, M.T.…”
Section: Semantic Assessmentmentioning
confidence: 99%